Domestic tourists' satisfaction towards museums in Melaka / Shareenie Shera Abdul Hamid...[et_al] - Abdul Hamid, Shareenie Shera (Research Management Institute (RMI), 2012)
Enjoying the declaration as Melaka Maju 2010 (Developing Melaka), the state has shown its maturity in tandem with its rapid development and economic stability. Melaka is endowed with a beautiful natural environment, rich with a mixture of cultures and lifestyles. As a World Heritage Site (UNESCO 2008), the growth of tourism in the state has contributed to better economic situation whereby more locals enjoy wider employment opportunities, generating higher income for the state. With a tagline "Visiting Melaka means Visiting Malaysia" undoubtedly, Melaka is a unique destination for heritage tourism. The National Trust for Historic Preservation defines heritage tourism as "travelling to experience the places, artifacts and activities that authentically represent the stories and people of the past and present." Focusing on the museums, the research attempts to explore the domestic tourists' satisfaction towards Melaka museums, as the researchers believe museum plays a major role in interpreting the heritage of Melaka. Hence, it is vital for the state administration to monitor the performance of the museums: its display items, maintenance, customer service, facilities as well as the local narratives so that museums can capture the interest of the public. Among almost thirty museums in Melaka, five museums were selected for the study; Muzium Belia Malaysia, Muzium Sejarah dan Ethnografi, Muzium Samudera, Muzium Setem Melaka as well as Muzium Kesultanan Melaka. Specific research objectives include: (1) to identify the attributes that fulfil the needs and wants of the domestic tourists (2) to scrutinize the domestic tourists' satisfaction level on gaining knowledge while visiting museums. The methodology proposed for this study is through a quantitative study whereby it will include both exploratory and descriptive. It is our hope that the outcomes of the study may help the tourism marketers have better ideas on the tourists expectations, develop appropriate strategies to attract their visitors besides than to serve them effectively. By having better understanding on these areas, it is not only reduces the marketing costs of the museums but on the other hand maintain heritage destinations' sustainability. Furthermore, this study contributes to the body of knowledge in satisfaction research. The findings should strengthen knowledge about the relationship between the factors that satisfy tourists and tourists' behaviors after exploring cultural/heritage tourism products.